Registration of a hard red winter wheat genetic stock homozygous for ph1b for facilitating alien introgression for crop improvement - Friebe, Bernd R.; Qi, Lili; Liu, Cheng; Liu, Wenxuan; Gill, Bikram S. (My University, 2012)
Wild relatives of bread wheat, Triticum aestivum L. are an important source for disease and pest resistance that can be exploited in wheat improvement. However, in wheat/alien species hybrids the pairing homoeologous gene, Ph1, suppresses the pairing and recombination of wheat and alien chromosomes and, thus, no alien genetic transfer can occur. However, in plants nullisomic for the Ph1 gene, and in the ph1b mutant stock, having a large deletion at the Ph1 locus, homoeologous wheat and alien chromosomes can pair and recombine. The original ph1b mutant stock is in Chinese Spring background, which has poor agronomic characteristics and several backcrosses with adapted wheat cultivars are necessary before the agronomic performance of the recombinants can be evaluated. The present report describes the transfer and characterization of the ph1b mutant allele into adapted Kansas winter wheat, which will accelerate the evaluation and utilization of wheat alien recombinants in cultivar improvement.
Citation: Friebe, B., Qi, L., Liu, C., Liu, W., & Gill, B. S. (2012). Registration of a hard red winter wheat genetic stock homozygous for ph1b for facilitating alien introgression for crop improvement. Retrieved from http://krex.ksu.edu
Keywords: Crop cytology; Crop genetics; Wheat